The coefficients of a quadratic function including the constant term, are all rational. The function satisfies the following conditions:
Find the value of
This problem is a part of <Christmas Streak 2017> series .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f ( x ) = a x 2 + b x + c , then f ′ ( x ) = 2 a x + b and f ′ ′ ( x ) = 2 a .
Now take a look at h ( x ) = f ′ ( x ) e f ( x ) . Note that h ′ ( x ) = { f ′ ( x ) 2 + f ′ ′ ( x ) } e f ( x ) .
There is exactly one root of h ( x ) = 0 , call it x = α . We know that f ′ ( α ) = 0 , and thus h ′ ( α ) = f ′ ′ ( α ) e f ( α ) = 0 .
Therefore g ( x ) = ∣ f ′ ( x ) ∣ e f ( x ) = ∣ h ( x ) ∣ is not differentiable at x = α .
Considering lim x → ± ∞ f ( x ) diverges to either infinity, lim x → ± ∞ g ( x ) diverges to either positive infinity or 0.
From [2.] g ( x ) has a maximum, which forces lim x → ± ∞ g ( x ) = 0 . This states that a < 0 .
Then, h ′ ( x ) = { ( 2 a x + b ) 2 + 2 a } e f ( x ) has two x -intercepts.
These informations let us to realize that h ( x ) has one local minimum and one local maximum, respectively negative and positive.
This forces g ( x ) = ∣ h ( x ) ∣ to only have maxima within where it is differentiable.
However [3.] states that g ( x ) has a minimum at x = 2 . This forces that α = 2 , leading to b = − 4 a .
Now let f ( x ) = a x 2 − 4 a x + c = a ( x − 2 ) 2 − 4 a + c . We can also say that f ′ ( x ) = 2 a ( x − 2 ) .
For g ( p ) = 4 e we have g ′ ( p ) = h ′ ( p ) = 0 .
g ( p ) = ∣ f ′ ( p ) ∣ e f ( p ) = 4 e , however p is rational, which forces f ′ ( p ) = ± 4 and f ( p ) = 2 1 .
h ′ ( p ) = { f ′ ( p ) 2 + f ′ ′ ( p ) } e f ( p ) = 0 ⇒ f ′ ′ ( p ) = − f ′ ( p ) 2 ⇒ 2 a = − 1 6 ⇒ a = − 8 .
f ( x ) = − 8 ( x − 2 ) 2 + k and f ′ ( x ) = − 1 6 ( x − 2 ) where f ′ ( p ) = − 1 6 ( p − 2 ) = ± 4 so that ( p − 2 ) 2 = 1 6 1 .
f ( p ) = − 8 ( p − 2 ) 2 + k = 2 1 , and so k = 1 .
∴ f ( x ) = − 8 ( x − 2 ) 2 + 1 ⇒ ∣ f ( − 1 ) ∣ = 7 1 .